Reporting mental health problems of undocumented migrants in Greece: A qualitative exploration. (2nd April 2016) - Teunissen, Erik; Tsaparas, Alexandra; Saridaki, Aristoula; Trigoni, Maria; van Weel-Baumgarten, Evelyn; van Weel, Chris; van den Muijsenbergh, Maria; Lionis, Christos
Abstract: Background: Mental health problems are highly prevalent amongst undocumented migrants (UMs), and often part of their consultations with general practitioners (GPs). Little empirical data are available of how GPs and UMs engage around mental health in Greece, a country with a lack of balance between primary and secondary care and limited healthcare provisions for UMs. Objectives: To acquire insight in the barriers and levers in the provision of mental healthcare for UMs by GPs in Greece. Methods: This was a qualitative study using semi-structured interviews with 12 GPs in Crete, Greece with clinical expertise in the care of UMs. All interviews were audio-taped and transcribed verbatim and were analysed using thematic content analysis. Results: Greek GPs recognized many mental health problems in UMs and identified the barriers that prevented them from discussing these problems and delivering appropriate care: growing societal resistance towards UMs, budget cuts in healthcare, administrative obstacles and lack of support from the healthcare system. To overcome these barriers, Greek GPs provided UMs with free access to care and psychotropic drugs free of charge, and referred to other primary care professionals rather than to mental healthcare institutions. Conclusion: Greek GPs experienced substantial barriers in the provision of mental healthcare to UMs and political, economic and organizational factors played a major role.